Growth, Mortality, and Exploitation Rate of Penaeus merguensis in the North Coast of Central Java, Indonesia - Suradi Wijaya Saputra; Anhar Solichin; Wiwiet Teguh Taufani (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
One of the most-caught shrimp in north coast of Central Java is Penaeus merguiensis. However, little is known on the population biology of the organisms. This study was aimed to investigate length-weight relationship, growth, length at first capture (Lc50), mortality rate, and exploitation rate of P. merguiensis in Western part of Central Java’s northern coastal waters. The study was conducted from May 2016 to July 2017 using survey method. Samples were taken for 15 times (month) from 9 coastal fishing ports. The result shows that the relationship of the carapace length and weight is negative allometry. The growth parameters of CL∞ and K were 52.5mm and 1.3 y-1 (male) and 57.25mm and 1.2 y-1 (female). Total mortality rate (Z), natural mortality rate (M), and fishing mortality rate (F) were 4.51 y-1, 1.86 y-1 and 2.65 y-1 (male), and 5.36 y-1, 1.72 y-1, and 3.64 y-1 (female), respectively. The exploitation rate (E) of male banana shrimp was 0.59, and for female shrimp was 0.68. The result shows that the exploitation level has exceeded the optimum level (E>0.5). Recruitment of P. merguiensis may occur the whole year, but it peaks were in March and August (male), April and August (female). Carapace length of first captured (CLc50) was 20.63mm (male) and 18.28mm (female). It means that the sized of captured P. merguiensis is less than the size of first mature (CLm50) or growth overfishing and as a result, disrupting the availability of adult shrimp. The condition occurs due to the size of cod-end mesh measured 0.75inc.